Assassin's strike - Larsen, Ward (A David Slaton novel, 2020)
"In a Syrian palace, the presidents of Russia and Syria undertake a clandestine meeting. No staff or advisors are permitted in the room. No records are kept. By necessity, however, there are two witnesses: the interpreters. The Russian, Ludmilla Kravchuk, returns to her hotel room burdened by what she has heard. When her Syrian counterpart is murdered before her eyes, Kravchuk fears she is next and goes into hiding in Syria. The CIA gets word of the defection. Desperate to uncover the purpose of the meeting, they task their newest off-the-books operator-legendary assassin David Slaton-to undertake a daring rescue. A thousand miles south, in the lawless reaches of Darfur, a cattle herder and his son stumble upon a deadly cache of chemical weapons. Their horrible deaths are soon uncovered, and evidence ties the tragedy to Slaton's mission. Behind the conspiracy is a shadowed figure: he claims to be the fifth Rashidun of Islam, but his true identity is even more stunning. The spectacular attack he is planning will tear the Middle East apart and return a notorious clan to power. Only one person stands in his way-Slaton. An assassin without peer"--